Improving Students’ Ability in Writing Recount Text through Project-Based Learning with Culturally Responsive Teaching - Suari, Ine; Aminah, Aminah; Sudamara, Yamon (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2025)
Writing skills represent a fundamental component of language learning that significantly influences students' academic achievement, yet EFL students encounter substantial challenges in writing recount texts. This study aimed to improve students' ability in writing recount texts through the implementation of Project-Based Learning (PjBL) integrated with Culturally Responsive Teaching (CRT). The research employed a Classroom Action Research (CAR) design using the Kemmis and McTaggart model implemented across two cycles. The population consisted of all eighth-grade students at SMP Negeri Model Terpadu Madani Palu, with a sample of 32 students selected through purposive sampling technique. Research instruments included writing tests using Jacobs et al. analytical rubric, observation sheets, and field notes. Quantitative data were analyzed using descriptive statistics, while qualitative data underwent thematic analysis. The results demonstrated significant improvement in students' writing abilities, with class mean scores increasing from 65.2 in the pre-cycle to 80.6 in Cycle II, while the percentage of students achieving the Minimum Mastery Criterion rose from 18.75% to 81.25%. The study concludes that integrating PjBL with CRT proves effective in enhancing EFL students' recount text writing abilities while developing their motivation, collaboration skills, and cultural awareness.